Réponses

Meilleure réponse !
2014-09-14T15:58:08+02:00
A = 36 - 6 x 4
A = 36 - 24
A = 12

B = (4 - 2/3) (2 - 4/3)
B = (4 x 3 / 1 x 3 - 2/3) (2 x 3 / 1 x 3 - 4/3)
B = (12/3 - 2/3) (6/3 - 4/3)
B = 10/3 x 2/3
B = 20/9

C = 10 + 5
       10 - 5
C = 15/5
C = 5 x 3 / 5 x 1
C = 3/1
C = 3

D = 2 + 1/3
       1/3 - 1
D = 2 x 3 / 1 x 3 + 1/3
       1/3 - 1 x 3 / 1 x 3
D = 6/3 + 1/3
       1/3 - 3/3
D = 7/3 : - 2/3
D = 7/3 x - 3/2
D = - 21/6
D = 3 x - 7 / 3 x 2
D = - 7/2
2014-09-14T17:27:36+02:00
A = 36 - 24 --> A = 12
B = (10/3)(2/3) --> B = 20/9
C = 15/5 --> C = 3
D = (7/3)/(-2/3) --> D = -7/2 ou -3,5